Concurrency control by Multiple Granularity of Locks in Multiusers Database Environment - Singh, Anil Kumar (International Journal of Computer Sciences and Engineering, 2018)
Concurrency control is a big problem in shared database system. The management of the concurrent execution of transactions in a multiuser database system is recognized as concurrency control. The aim of concurrency control is to confirm the serializability of transactions in a multiuser database situation. It is significant because the simultaneous execution of transactions over a shared database can create several data integrity and consistency problems i.e. problem of summarization and problem of maintaining statistics. Multiple granularity means which level lock will apply, if we apply the lock on exact level of database, then definitely we may control the concurrency. In this paper we shall reveal in which level lock should apply for prevent above mentioned problems. With the help of Multiple Granularity, we shall reveal how to prevent the problem arise due to concurrency with the help of suitable examples. It will help the students and research scholars to understand that how to prevent the concurrency problems with the help of Multiple Granularity Locking Protocol method.